Managing changes in requirements: an empirical investigation. Issue 12 (5th June 2013) - Janes, Andrea; Remencius, Tadas; Sillitti, Alberto; Succi, Giancarlo
ABSTRACT This paper describes the challenges of handling changing requirements in software companies. This empirical investigation deals with the different sources of changes and with the different approaches to requirements evolution. We have considered the point of view of 35 managers of software companies interviewed through a questionnaire. The final results highlight some areas to improve requirements engineering and requirements management. Copyright © 2013 John Wiley & Sons, Ltd.